FORMATIVE ASESSMENT IN INDEPENDENT CURRICULUM FOR PRIMARY SCHOOL IN UPT SD NEGERI 224 GRESIK - Septiarini, Nur Leni (Journal in Teaching and Education Area, 2024)
This study aims to find out the implementation of evaluation in the teaching of English in the Independent Curriculum at the UPT SDN 224 Gresik. This study investigates the application of the formative evaluation of English teaching in the Curriculum. This research uses case studies. The subjects of this study are two first- and third-grade English teachers as well as students of the first and third classes. Data is collected and analyzed using qualitative methods. Observations and interviews are used to gather data. This study uses the theory of Miles and Huberman (1994). This research reveals that teachers have a fairly optimal formative implementation. Teachers use performance through presentation and role-play for formative assessment. Even the teacher gives feedback on the student's evaluation results. The teacher really understands the application and function of the formative assessment even assesses and assumes that the formation of the assessment is more important than the sumative.